Perancangan dan Analisis Kerja Mobile Jammer Tipe D dengan Sensor Sinyal Berbasis Mikrokontroler untuk Jaringan GSM 900 - Dedy Wahyu Herdianto; Satryo Budi Utomo; Catur Suko Sarwono (Jurnal Arus Elektro Indonesia, 2015)
AbstractMobile Jammer is a tool used to transmitting electromagnetic signal in selular frequency. There are many types of mobile jammer, one of it is type D which able to select interfered signal using a sensor. The sensor will receive GSM signal sent as an input for the jammer’s activator.This sensor consist of two IC CA3130, IC555 and microcontroller ATMega8 and This research purpose is to combine the jammer for GSM signal and microcontroller as the control. The result of this research is showing that the system that we created was able to perfectly working 100 %. It’s shown 100% successful rate for the length of 5 to 7 meters in the field test for three providers which are Telkomsel, Indosat and XL.Keywords— Mobile jammer, GSM, Signal Sensor, Microcontroller.